Phylogenomic Analyses of Hepatica Species and Comparative Analyses Within Tribe Anemoneae (Ranunculaceae) - Park, Kyu Tae; Park, SeonJoo (Frontiers in Plant Science, 2021)
Hepatica is a small genus of Ranunculaceae with medicinal and horticultural value. We characterized nine complete chloroplast (cp) genomes of Hepatica, which ranged from 159,549 to 161,081 bp in length and had a typical quadripartite structure with a large single-copy region (LSC; 80,270 ~ 81,249 bp), the small single-copy region (SSC; 17,029 ~ 17,838 bp), and two copies of the inverted repeat (IR; 31,008 ~ 31,100 bp). The cp genomes of Hepatica possess 76 protein-coding genes, 29 tRNAs, and four rRNA genes. Comparative analyses revealed a conserved ca. 5 kb IR expansion in Hepatica and other Anemoneae; moreover, multiple inversion events occurred in Hepatica and its relatives. Analyses of selection pressure (dN/dS) showed that most of the protein-coding genes (PCGs) are highly conserved except for rpl20 and rpl22 in H. falconeri, H. americana, and H. acutiloba. Two genes (rps16 and infA) were identified as pseudogenes in Hepatica. In contrast, rpl32 gene was completely lost. The phylogenetic analyses based on 76 PCGs resolved the phylogeny of Hepatica and its related genera. Non-monophyly of Anemone s.l. indicates that Hepatica should be reclassified as an independent genus. In addition, H. nobilis var. japonica is not closely related to H. nobilis.